Composite diaphragm, battery and electric equipment

By setting the porosity gradient of the electrolyte layer in the separator of the lithium secondary battery, the shortcomings of the existing separator in terms of wetting ability and thermal stability are solved, and the electrical and safety performance of the battery are significantly improved.

CN119764755APending Publication Date: 2025-04-04BYD CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411923026.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The separators of existing lithium secondary batteries have insufficient in terms of wetting ability and thermal stability of ionic liquids or high viscosity liquid electrolytes, which affect the electrical and safety performance of the battery.

Method used

A composite separator is adopted, which includes a base film and an electrolyte layer. The electrolyte layer is set on one side of the base film, and the porosity near the base film is smaller than the porosity far away from the base film. Through this structure, the wetting and liquid retention of the electrolyte solution are improved while enhancing the mechanical strength of the electrolyte layer.

Benefits of technology

The wetting, liquid retention and thermal stability of the composite separator are improved, thereby improving the electrical and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764755A_ABST
    Figure CN119764755A_ABST
Patent Text Reader

Abstract

The invention discloses a composite diaphragm, a battery and electric equipment, the composite diaphragm comprises a base membrane and an electrolyte layer, the electrolyte layer is arranged on at least one side surface of the base membrane in the thickness direction, and the electrolyte layer comprises electrolyte particles, the porosity of the electrolyte layer close to one side of the base membrane is smaller than that of the electrolyte layer far away from one side of the base membrane. According to the composite diaphragm disclosed by the invention, the wettability, the liquid retention property and the thermal stability of the composite diaphragm can be effectively improved, so that the electrical property and the safety performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a composite diaphragm, a battery and an electrical device. Background Art

[0002] In order to improve the safety of the battery, the separator of the lithium secondary battery can be impregnated with an ionic liquid or a high-viscosity liquid electrolyte. In the conventional technology, a polypropylene or polyethylene microporous membrane separator is usually used, and the ionic liquid or high-viscosity liquid electrolyte of the above separator has poor wetting ability. In addition, there is also the problem of poor thermal stability. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one object of the present invention is to provide a composite diaphragm that can effectively improve the wettability, liquid retention and thermal stability of the composite diaphragm, thereby improving the electrical performance and safety performance of the battery.

[0004] The second object of the present invention is to provide a battery using the above composite separator.

[0005] The third object of the present invention is to provide an electrical device using the above battery.

[0006] According to the composite diaphragm of the first aspect of the present invention, the composite diaphragm includes: a base membrane; an electrolyte layer, wherein the electrolyte layer is arranged on at least one side surface of the base membrane in the thickness direction, the electrolyte layer includes electrolyte particles, and the porosity of the electrolyte layer close to the base membrane is smaller than the porosity of the electrolyte layer away from the base membrane.

[0007] According to the composite diaphragm of the embodiment of the present invention, by setting different porosities on the electrolyte layer near the base membrane and away from the base membrane, the electrolyte wettability and liquid retention of the composite diaphragm are improved, while the mechanical strength of the composite electrolyte layer can be improved, thereby improving the thermal stability of the composite diaphragm and improving the electrical performance and safety performance of the battery.

[0008] According to some embodiments of the present invention, micropores are formed on the base film, and the maximum width of the electrolyte particles is greater than the maximum width of the micropores.

[0009] According to some embodiments of the present invention, the porosity of the electrolyte layer gradually increases along a direction from the base membrane toward the electrolyte layer.

[0010] According to some embodiments of the present invention, the porosity of the electrolyte layer is v, wherein v satisfies: 20%≤v≤90%.

[0011] According to some embodiments of the present invention, v satisfies: 30%≤v≤60%.

[0012] According to some embodiments of the present invention, the particle size of the electrolyte particles is d, wherein d satisfies: 0.01 μm≤d≤100 μm.

[0013] According to some embodiments of the present invention, the particle size of the electrolyte particles close to the base membrane is smaller than the particle size of the electrolyte particles far from the base membrane.

[0014] According to some embodiments of the present invention, the particle size of the electrolyte particles gradually increases along the direction from the base membrane toward the electrolyte layer.

[0015] According to some embodiments of the present invention, the electrolyte layer includes at least: a first electrolyte layer, the first electrolyte layer is arranged on at least one side surface of the base membrane in the thickness direction, the first electrolyte layer includes first electrolyte particles; a second electrolyte layer, the second electrolyte layer is arranged on a side of the first electrolyte layer away from the base membrane, the second electrolyte layer includes second electrolyte particles, and the particle size of the second electrolyte particles is larger than the particle size of the first electrolyte particles.

[0016] According to some embodiments of the present invention, the particle size of the first electrolyte particles is d1, wherein d1 satisfies: 0.01 μm≤d1≤3 μm.

[0017] According to some embodiments of the present invention, the particle size of the second electrolyte particles is d2, wherein d2 satisfies: 1 μm≤d2≤100 μm.

[0018] According to some embodiments of the present invention, a mass proportion of the first electrolyte particles in the first electrolyte layer is greater than a mass proportion of the second electrolyte particles in the second electrolyte layer.

[0019] According to some embodiments of the present invention, the thickness of the composite membrane is h3, wherein h3 satisfies: 0.1 μm≤h3≤1 mm.

[0020] According to some embodiments of the present invention, the electrolyte layer includes a binder, and the electrolyte layer includes: 0.1% to 99% of the electrolyte particles, and 1% to 99.9% of the binder, by mass percentage.

[0021] According to some embodiments of the present invention, the electrolyte layer comprises, by mass percentage: 1% to 80% of the electrolyte particles, and 20% to 99% of the adhesive.

[0022] According to some embodiments of the present invention, the adhesive includes at least one of vinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, polyethylene oxide, carboxymethyl cellulose, sodium alginate, polyacrylic acid, polyamide, polyvinyl alcohol, polyethylene imine and polyimide.

[0023] According to some embodiments of the present invention, the solid electrolyte particles include at least one of an inorganic ceramic oxide solid electrolyte, an organic-inorganic composite solid electrolyte, and an organic polymer solid electrolyte.

[0024] According to some embodiments of the present invention, the inorganic ceramic oxide solid electrolyte includes at least one of a perovskite-type solid electrolyte, a garnet-type solid electrolyte, an amorphous oxide solid electrolyte, a lithium superion conductor-type solid electrolyte, and a sodium superion conductor-type solid electrolyte; and / or, the organic-inorganic composite solid electrolyte includes a polyethylene oxide solid electrolyte, an oxide-polymer composite solid electrolyte, a sulfide-polymer composite solid electrolyte; and / or, the organic polymer solid electrolyte includes a polymer solid electrolyte, a covalent organic framework solid electrolyte, a polycarbonate solid electrolyte, a polyether solid electrolyte, or an organic ionic crystal electrolyte.

[0025] According to some embodiments of the present invention, the base film includes at least one of a polyethylene film, a polypropylene film, a polyvinylidene fluoride film, an aramid film, a polyacrylonitrile film, a polyimide film, a polyamide film, a polyester film, and a natural fiber film.

[0026] A battery according to an embodiment of the second aspect of the present invention comprises the composite separator according to the embodiment of the first aspect.

[0027] The electrical equipment according to the third aspect of the present invention comprises the battery according to the second aspect of the present invention.

[0028] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 is a schematic diagram of a composite diaphragm according to an embodiment of the present invention; Figure 2 is a schematic diagram of a composite diaphragm according to another embodiment of the present invention; Figure 3 is a schematic diagram of a composite membrane according to another embodiment of the present invention.

[0030] Reference numerals: 100. Composite diaphragm; 1. Basement membrane; 11. Micropores; 2. electrolyte layer; 21. electrolyte particles; 22. adhesive; 23. first electrolyte layer; 231. first electrolyte particles; 24. Second electrolyte layer; 241. Second electrolyte particles. DETAILED DESCRIPTION

[0031] The embodiments of the present invention are described in detail below. The embodiments described with reference to the accompanying drawings are exemplary. Figure 1 and Figure 3 The composite separator 100 according to the first embodiment of the present invention is described. In the following description of the present application, the composite separator 100 is used in a battery as an example.

[0032] like Figure 1 and Figure 2 As shown, the composite membrane 100 according to the first embodiment of the present invention includes a base membrane 1 and an electrolyte layer 2 .

[0033] Specifically, the electrolyte layer 2 is disposed on at least one surface of the base membrane 1 in the thickness direction, and the electrolyte layer 2 includes electrolyte particles 21 . The porosity of the electrolyte layer 2 close to the base membrane 1 is smaller than the porosity of the electrolyte layer 2 away from the base membrane 1 .

[0034] For example, the electrolyte layer 2 may be provided only on one side of the base film 1 in the thickness direction, or the electrolyte layer 2 may be provided on both sides of the base film 1 in the thickness direction. The electrolyte layer 2 may improve the ion conductivity of the battery, accelerate the transmission of lithium ions, improve the ion conductivity, and thus improve the charge and discharge performance and cycle performance of the battery. A plurality of electrolyte particles 21 are dispersed in the electrolyte layer 2. The gaps between the electrolyte particles 21 close to the base film 1 along the thickness direction of the electrolyte layer 2 are smaller than the gaps between the electrolyte particles 21 away from the base film 1. It should be noted that the porosity of the electrolyte layer 2 refers to the volume ratio of the pores in the electrolyte layer 2 as a whole formed by the gaps between the plurality of electrolyte particles 21 in the electrolyte layer 2.

[0035] In this way, the porosity of the electrolyte layer 2 on the side away from the base membrane 1 is high, which is conducive to the electrolyte infiltration of the electrolyte layer, and can improve the electrolyte wettability and liquid retention of the composite diaphragm 100. In addition, the porosity of the electrolyte layer 2 on the side close to the base membrane 1 is low, which can improve the mechanical strength of the composite electrolyte layer 2, thereby improving the thermal stability of the composite diaphragm 100, and improving the electrical performance and safety performance of the battery.

[0036] According to the composite diaphragm 100 of the embodiment of the present invention, by setting different porosities on the electrolyte layer 2 near the base membrane 1 and away from the base membrane 1, the electrolyte wettability and liquid retention of the composite diaphragm 100 are improved, while the mechanical strength of the composite electrolyte layer 2 can be improved, thereby improving the thermal stability of the composite diaphragm 100 and improving the electrical performance and safety performance of the battery.

[0037] According to some embodiments of the present invention, micropores 11 are formed on the base film 1, and the maximum width of the electrolyte particles 21 is greater than the maximum width of the micropores 11. The maximum width of the electrolyte particles 21 refers to the maximum width of the maximum cross-sectional area of ​​the electrolyte particles 21, and the maximum width of the micropores 11 refers to the maximum width of the maximum cross-sectional area of ​​the micropores 11. For example, in Figure 1 and Figure 2 In the example, the micropores 11 penetrate the two side surfaces of the base film 1 in the thickness direction. The electrolyte particles 21 can be particles of various shapes, such as spherical, rectangular or irregular shapes. Therefore, by setting the maximum width of the electrolyte particles 21 to be greater than the maximum width of the micropores 11, the electrolyte particles 21 are not easily blocked in the micropores 11 of the body, which has the effect of improving ion conductivity and can also effectively inhibit the local growth of lithium dendrites.

[0038] According to some embodiments of the present invention, the porosity of the electrolyte layer 2 gradually increases along the direction of the base membrane 1 toward the electrolyte layer 2. The gradual increase in the porosity of the electrolyte layer 2 can also be understood as: the porosity on the electrolyte layer 2 of the composite diaphragm 100 is distributed in a gradient along the thickness direction of the electrolyte layer 2. Of course, the above-mentioned "gradual increase in porosity" can be a linear growth or a nonlinear growth. Along the thickness direction of the electrolyte layer 2, the porosity of the electrolyte layer 2 close to the side of the base membrane 1 is relatively small, and the porosity of the electrolyte layer 2 away from the side of the base membrane 1 is relatively large. In this way, along the direction of the base membrane 1 toward the electrolyte layer 2, the electrolyte wetting performance and liquid retention performance of the electrolyte layer 2 are gradually improved, and at the same time, the mechanical structure strength of the electrolyte layer 2 is gradually reduced. That is to say, the comprehensive performance of the electrolyte layer 2 is improved, and it has higher electrolyte wetting performance and liquid retention performance, while also having better thermal stability.

[0039] According to some embodiments of the present invention, the porosity of the electrolyte layer 2 is v, wherein v satisfies: 20% ≤ v ≤ 90%. That is, the porosity of the pores of the electrolyte layer 2 is distributed in the range of 20% to 90% along the thickness direction of the electrolyte layer 2. Thus, the setting of the porosity of the electrolyte layer 2 is reasonable, which is conducive to the performance of the electrolyte layer 2, and thus more conducive to the use of the composite diaphragm 100. Preferably, v further satisfies: 30% ≤ v ≤ 60%. Thus, the setting of the porosity of the electrolyte layer 2 is more reasonable, which is more conducive to the performance of the composite diaphragm 100.

[0040] According to some embodiments of the present invention, the particle size of the electrolyte particles 21 is d, where d satisfies: 0.01μm≤d≤100μm. For example, a plurality of electrolyte particles 21 are dispersed in the electrolyte layer 2, and a large number of electrolyte particles 21 are also dispersed in the same plane at the same distance from the base membrane 1. The closer the electrolyte particles 21 are to the base membrane 1, the smaller the particle size. The particle size distribution range of all electrolyte particles 21 is 0.01μm~100μm. Therefore, the particle size of the electrolyte particles 21 is reasonably set, so that the electrolyte layer 2 has reasonable structural strength while also having better electrolyte wettability and liquid retention, which is beneficial to the performance of the electrolyte layer 2. Preferably, d further satisfies: 1μm≤d≤10μm.

[0041] According to some embodiments of the present invention, the particle size of the electrolyte particles 21 on the side close to the base membrane 1 is smaller than the particle size of the electrolyte particles 21 on the side away from the base membrane 1. For example, when the shape of the electrolyte particles 21 is spherical, the smaller the particle size of the electrolyte particles 21, the smaller the porosity under the same volume. In other words, the particle sizes of the multiple electrolyte particles 21 of the electrolyte layer 2 are different, and the particle size of the electrolyte particles 21 on the side close to the base membrane 1 is smaller to enhance the structural strength of the electrolyte layer 2. The particle size of the electrolyte particles 21 on the side away from the base membrane 1 is larger to facilitate the infiltration of the liquid. It should be noted that the particle size in this application refers to Dn 50 , which can be measured using a laser particle size analyzer.

[0042] According to some embodiments of the present invention, the particle size of the plurality of electrolyte particles 21 gradually increases along the direction from the base film 1 to the electrolyte layer 2. For example, along the direction from the base film 1 to the electrolyte layer 2, the particle size of the plurality of electrolyte particles 21 is distributed in a gradient. Of course, the above-mentioned "gradual increase in particle size" can be linear or nonlinear. Thus, it is beneficial to the performance of the electrolyte layer 2 and the use of the composite separator 100.

[0043] According to some embodiments of the present invention, Figure 1 and Figure 2 The electrolyte layer 2 at least includes a first electrolyte layer 23 and a second electrolyte layer 24. The first electrolyte layer 23 is provided on at least one side surface of the base film 1 in the thickness direction, and the first electrolyte layer 23 includes first electrolyte particles 231. The second electrolyte layer 24 is provided on a side of the first electrolyte layer 23 away from the base film 1, and the second electrolyte layer 24 includes second electrolyte particles 241. The particle size of the second electrolyte particles 241 is larger than that of the first electrolyte particles 231.

[0044] For example, in Figure 1 and Figure 2In the example, the first electrolyte particles 231 and the second electrolyte particles 241 are multiple. The electrolyte layer 2 is a double-layer structure including the first electrolyte layer 23 and the second electrolyte layer 24. Of course, the electrolyte layer 2 can also be set to a three-layer structure or a layer structure with more layers according to the use requirements. A plurality of first electrolyte particles 231 are dispersed in the first electrolyte layer 23, and a plurality of second electrolyte particles 241 are dispersed in the second electrolyte layer 24. The electrolyte particles 21 can be particles of various shapes, such as spherical, rectangular or irregular shapes. When the electrolyte particles 21 are spherical particles or particles similar to spherical shapes, the particle diameter of the second electrolyte particles 241 is greater than the particle diameter of the first electrolyte particles 231. In this way, the particle size gradient arrangement of the electrolyte particles 21 of the electrolyte layer 2 is realized, that is, the particle size of the electrolyte particles 21 far away from the base film 1 is greater than the particle size of the electrolyte particles 21 adjacent to the base film 1, so as to improve the electrolyte wettability and liquid retention of the composite diaphragm 100, and also improve the mechanical strength of the composite electrolyte layer 2, and improve the electrical performance and safety performance of the battery. Of course, the present application takes the electrolyte layer 2 including the first electrolyte layer 23 and the second electrolyte layer 24 as an example for explanation, but is not limited thereto. The electrolyte layer 2 may be a multi-layer structure.

[0045] According to some embodiments of the present invention, the particle size of the first electrolyte particle 231 is d1, wherein d1 satisfies: 0.01 μm≤d1≤3 μm. It should be noted that the particle size in the entire application refers to Dn 50 , which can be measured by a laser particle size analyzer. For example, when the particle size of the first electrolyte particle 231 is less than 0.01 μm, the particle size of the first electrolyte particle 231 is too small, which increases the precision requirement for the first electrolyte particle 231, and the porosity of the first electrolyte layer 23 is too low, and the first electrolyte particle 231 is also easily blocked in the micropores 11 on the base film 1. When the particle size of the first electrolyte particle 231 is greater than 3 μm, the porosity of the first electrolyte layer 23 increases, which reduces the mechanical strength of the first electrolyte layer 23. Therefore, by setting the particle size d1 of the first electrolyte particle 231 to meet 0.01 μm≤d1≤3 μm, the particle size of the first electrolyte particle 231 is reasonably set, so that the first electrolyte layer 23 has a reasonable porosity and a certain mechanical strength, which is conducive to the performance of the first electrolyte layer 23. Preferably, d1 satisfies: 0.05 μm≤d1≤1 μm, which further optimizes the performance of the first electrolyte layer 23, thereby being more conducive to the use of the composite diaphragm 100.

[0046] According to some embodiments of the present invention, the particle size of the second electrolyte particle 241 is d2, wherein d2 satisfies: 1μm≤d2≤100μm. For example, when the particle size of the second electrolyte particle 241 is less than 1μm, the particle size of the second electrolyte particle 241 is too small, which reduces the porosity of the first electrolyte layer 23 and reduces the electrolyte wettability and liquid retention of the composite diaphragm 100. When the particle size of the second electrolyte particle 241 is greater than 100μm, the porosity of the second electrolyte layer 24 is large, which reduces the mechanical strength of the second electrolyte layer 24. Therefore, by setting the particle size d2 of the second electrolyte particle 241 to satisfy 1μm≤d2≤100μm, the particle size of the second electrolyte particle 241 is reasonably set, so that the second electrolyte layer 24 has a reasonable porosity while also having better electrolyte wettability and liquid retention, which is conducive to the performance of the second electrolyte layer 24. Preferably, d2 satisfies: 1 μm≤d1≤50 μm, which further optimizes the performance of the second electrolyte layer 24 and is more conducive to the use of the composite separator 100 .

[0047] According to some embodiments of the present invention, the mass proportion of the first electrolyte particles 21 in the first electrolyte layer 23 is greater than the mass proportion of the second electrolyte particles 241 in the second electrolyte layer 24. In other words, the ratio of the sum of the masses of the plurality of first electrolyte particles 231 to the mass of the first electrolyte layer 23 is greater than the ratio of the sum of the masses of the plurality of second electrolyte particles 241 to the mass of the second electrolyte layer 24. In other words, the particle size of the first electrolyte particles 231 is relatively small, and the mass proportion is relatively high. The particle size of the second electrolyte particles 241 is relatively large, and the mass proportion is relatively low. In this way, the mass relationship between the first electrolyte particles 231 and the second electrolyte particles 241 is reasonably set, which is more conducive to the performance of the electrolyte layer 2, and further improves the electrical performance and safety performance of the battery.

[0048] According to some embodiments of the present invention, the thickness of the composite diaphragm 100 is h3, wherein h3 satisfies: 0.1 μm ≤ h3 ≤ 1 mm. For example, when the thickness of the composite diaphragm 100 is less than 0.1 μm, the thickness of the composite diaphragm 100 is small, which increases the difficulty of processing the composite diaphragm 100. When the thickness of the composite diaphragm 100 is greater than 1 mm, the thickness of the composite diaphragm 100 is large, which increases the space occupied by the composite diaphragm 100 in the battery. Therefore, by setting the thickness h3 of the composite diaphragm 100 to satisfy 0.1 μm ≤ h3 ≤ 1 mm, the thickness of the composite diaphragm 100 is reasonably set, which is conducive to the production and processing of the composite diaphragm 100, improves production efficiency, and is easy to use. Moreover, it also reduces the space occupied by the composite diaphragm 100 in the battery and improves the performance of the composite diaphragm 100. Preferably, h3 satisfies: 2 μm ≤ h3 ≤ 10 μm, so as to be more conducive to the use of the composite diaphragm 100.

[0049] According to some embodiments of the present invention, the electrolyte layer 2 includes a binder 22. By mass percentage, the electrolyte layer 2 includes: 0.1% - 99% of electrolyte particles 21 and 1% - 99.9% of the binder 22. For example, when the mass of the electrolyte particles 21 accounts for 0.1% of the total mass of the electrolyte layer 2, the mass of the binder 22 accounts for 99.9% of the total mass of the electrolyte layer 2. That is to say, the electrolyte layer 2 is formed by mixing the electrolyte particles 21 in the binder 22. Thus, the electrolyte particles 21 can be evenly dispersed in the binder 22, and at the same time, it is also beneficial for the electrolyte layer 2 to be coated and bonded on the surface of the base film 1. In addition, the components of the electrolyte layer 2 are few and the composition is simple, which is beneficial for the formation of the electrolyte layer 2. Preferably, by mass percentage, the electrolyte layer 2 includes: 1% - 80% of electrolyte particles and 20% - 99% of the binder.

[0050] According to some embodiments of the present invention, the electrolyte particles 21 include at least one of liquid electrolyte particles 21, solid electrolyte particles 21, and gel electrolyte particles 21. For example, the liquid electrolyte particles 21 include ionic liquids or polymer ionic liquids, etc. With such a setting, there are more types of electrolyte particles 21 suitable for the electrolyte layer 2, which reduces the precision requirements for the preparation of the electrolyte layer 2 and is more beneficial for the preparation of the electrolyte layer 2. Moreover, the processing cost of the electrolyte layer 2 can also be reduced. Preferably, the electrolyte particles 21 include solid electrolyte particles 21.

[0051] According to some alternative embodiments of the present invention, the solid electrolyte particles 21 include at least one of inorganic ceramic oxide solid electrolytes, organic-inorganic composite solid electrolytes, and organic polymer solid electrolytes. The inorganic ceramic oxide solid electrolytes include at least one of perovskite-type solid electrolytes, garnet-type solid electrolytes, amorphous oxide solid electrolytes, lithium superionic conductor-type solid electrolytes (LISICON type), and sodium superionic conductor-type solid electrolytes (NASICON type). And / or, the organic-inorganic composite solid electrolytes include polyethylene oxide solid electrolytes, oxide-polymer composite solid electrolytes, sulfide-polymer composite solid electrolytes. And / or, the organic polymer solid electrolytes include polymer solid electrolytes, covalent organic framework solid electrolytes, polycarbonate-based solid electrolytes, polyether-based solid electrolytes, or organic ion crystal electrolytes.

[0052] For example, the typical structure of the perovskite-type solid electrolyte is Li 3x La 2 / 3-x TiO3 (abbreviated as LLTO, 0 < x < 0.16) has the highest crystal conductivity among crystalline solid electrolytes, and when x = 0.11, its room temperature conductivity reaches the highest, and the crystal conductivity is 10 -3 S / cm; the garnet-type solid electrolyte is typically Li7La3Zr2O12 The cubic phase structure has higher conductivity than the tetragonal phase structure, and its crystal skeleton network is composed of La 3+ 、Zr 2+ and O 2- Ion composition, Li ions are distributed within the crystal grid. The shortest distance between adjacent Li ions is the main reason for rapid ion transport, and thus provides high ionic conductivity; NASICON-type solid electrolytes have ultra-high ionic conductivity, and have the advantages of stable structure, wide electrochemical window, environmental friendliness, and a wide operating temperature range. Therefore, the above-mentioned solid electrolyte particles 21 are widely available, easy to obtain, and have excellent performance, which is beneficial to the performance of the electrolyte layer 2, and is more conducive to the use and performance of the composite diaphragm 100. Preferably, the electrolyte particles 21 are inorganic ceramic oxide solid electrolytes or organic-inorganic composite solid electrolytes.

[0053] For example, oxide-polymer composite solid electrolytes use oxides as inorganic fillers, such as Al2O3, TiO2, LLZO, etc., and are composited with polymer matrices such as polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), etc. Sulfide-polymer composite solid electrolytes use Li2S, Li3PS4, etc. and polymers such as PEO. Metal fluoride-polymer composite solid electrolytes can be metal fluorides such as LiF, AlF3, etc. composited with polymers such as PEO. Polymer solid electrolytes can be: polymers such as polyethylene oxide (PEO), polyvinylidene fluoride (PVDF) as matrices, and lithium ion conduction is achieved by doping lithium salts.

[0054] According to some embodiments of the present invention, the base film 1 includes at least one of a polyethylene film, a polypropylene film, a polyvinylidene fluoride film, an aramid film, a polyacrylonitrile film, a polyimide film, a polyamide film, a polyester film and a natural fiber film. The base film 1 is a porous base film. In this way, the base film 1 has a wide range of material choices. The base film 1 made of the above materials has a good supporting effect, which is beneficial to the connection between the base film 1 and the electrolyte layer 2, and is more beneficial to the use of the base film 1. At the same time, the performance of the composite adhesive film can also be guaranteed.

[0055] According to some embodiments of the present invention, the adhesive 22 includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyethylene oxide (PEO), carboxymethyl cellulose (CMC / CMC-Li), sodium alginate, polyacrylic acid (PAA), polyamide (PAI), polyvinyl alcohol (PVA), polyethyleneimine (PEI) and polyimide (PI). In this way, by using the adhesive 22 of the above materials, it is beneficial for the electrolyte particles 21 to be evenly dispersed in the adhesive 22. In addition, it is also beneficial for the electrolyte layer 2 to cover and adhere to the surface of the base film 1, thereby facilitating the processing and preparation of the composite film. At the same time, it has no adverse effect on the performance of the electrolyte layer 2 and the composite film.

[0056] According to some embodiments of the present invention, referring to Figure 3 , electrolyte layers 2 are provided on both sides of the thickness direction of the base film 1. Figure 1 and Figure 3 In the example, the upper and lower surfaces of the base film 1 are respectively covered with the electrolyte layer 2. Thus, the performance of the composite separator 100 is further improved. When the composite separator 100 is used in a battery, the electrical performance and safety performance of the battery are further improved.

[0057] The battery according to the second embodiment of the present invention (not shown) comprises the composite separator 100 according to the first embodiment. The battery according to the embodiment of the present invention has excellent electrical and safety performance by adopting the composite separator 100, which is beneficial to the long-term use of the battery.

[0058] As an example, the battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a composite separator 100, and the composite separator 100 is located between the positive electrode sheet and the negative electrode sheet. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The composite separator 100 is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0059] According to an embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material. The positive electrode current collector may be a metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector), for example, the positive electrode current collector may be an aluminum foil.

[0060] In the embodiments of the present invention, the specific type of the positive electrode active material is not particularly limited. As some specific embodiments, the positive electrode active material includes at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium cobalt phosphate, lithium manganese phosphate, lithium nickel phosphate, lithium manganese oxide, binary materials, and ternary materials.

[0061] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorine-containing acrylate resin.

[0062] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0063] According to some embodiments of the present invention, a positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, a positive electrode sheet can be obtained.

[0064] According to an embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, wherein the negative electrode current collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the negative electrode current collector can be a copper foil.

[0065] According to some embodiments of the present invention, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc.

[0066] According to some embodiments of the present invention, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0067] According to some embodiments of the present invention, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg sodium carboxymethyl cellulose (CMC-Na)).

[0068] According to some embodiments of the present invention, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0069] According to some other embodiments of the present invention, the type of electrolyte is not specifically limited and can be selected according to needs. According to some specific embodiments of the present invention, the electrolyte is an electrolyte solution, and the electrolyte solution includes a lithium salt and a solvent.

[0070] According to some specific embodiments of the present invention, the lithium salt may include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium phosphate ester (LiBOB), lithium difluorophosphate (LiPO2F2).

[0071] According to some specific embodiments of the present invention, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone or diethyl sulfone.

[0072] In some embodiments of the present invention, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0073] The electric device according to the third embodiment of the present invention (not shown) comprises the battery according to the second embodiment of the present invention. The electric device according to the embodiment of the present invention improves the performance of the electric device by using the battery.

[0074] Specifically, the electrical equipment may be, but is not limited to, electric cars, battery cars, mobile phones, tablets, laptop computers, electric toys, ships, spacecraft, etc. Electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.

[0075] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention. In addition, if not explicitly stated, all reagents used in the following embodiments are commercially available, or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0076] The composite diaphragm 100 of the present invention is described by means of exemplary specific embodiments and comparative examples. The composite diaphragms of Examples 1 to 6 and Comparative Examples 1 to 5 are tested for related properties.

[0077] Among them, the thickness of the composite diaphragm 100 and the electrolyte layer are measured using a non-contact thickness gauge (accuracy 0.0001mm); the porosity of the electrolyte layer is tested according to (GB / T21650.2-2008 "Determination of pore size distribution and porosity of solid phase materials by mercury injection and gas adsorption method Part 2: Analysis of mesopores and macropores by gas adsorption method"); the conductivity of the electrolyte layer is tested using a four-probe test; according to (GB / T13519-2016 "Polyethylene heat shrinkable film for packaging"), the composite diaphragm is placed in a 90°C oven for 60 minutes to measure its heat shrinkage rate.

[0078] The contact angle of the composite diaphragm 100 is measured according to the static sessile drop method. A 2 μL electrolyte droplet is placed on the diaphragm surface using an optical contact angle tester, and the contact angle is measured by observing the contact between the droplet and the solid surface. A high-resolution camera is used to take a picture, and the sixth picture after the electrolyte contact is selected to measure the contact angle.

[0079] Example 1 Electrolyte layers 2 are provided on both sides of the base film 1 in the thickness direction, respectively. The electrolyte layer 2 includes a first electrolyte layer 23 and a second electrolyte layer 24 .

[0080] The preparation method of the electrolyte layer 2 comprises the following steps: 1. Preparation and coating of slurry of the first electrolyte layer 23 The inorganic ceramic oxide solid electrolyte Li7La3Zr2O with a particle size of 0.35 μm 12 (LLZO), PVDF, and NMP (N-methylpyrrolidone) are prepared in a mass ratio of 100:2.5:69 and mixed evenly to obtain LLZO slurry; the LLZO slurry is coated on the corresponding surface of the base film 1 (by gravure printing process) to form a 2μm thick first electrolyte layer 23 on the base film 1.

[0081] 2. Preparation and coating of slurry of the second electrolyte layer 24 The inorganic ceramic oxide solid electrolyte Li7La3Zr2O with a particle size of 1 μm 12 (LLZO), PVDF, and NMP are prepared in a mass ratio of 100:2.5:69 and mixed evenly to obtain a solid electrolyte slurry; the solid electrolyte slurry is coated on the first electrolyte layer 23 (using a gravure printing process) to form a 2 μm thick second electrolyte layer 24 on the surface of the first electrolyte layer 23.

[0082] Example 2 Electrolyte layers 2 are provided on both sides of the base film 1 in the thickness direction, respectively. The electrolyte layer 2 includes a first electrolyte layer 23 and a second electrolyte layer 24 .

[0083] The preparation method of the electrolyte layer 2 comprises the following steps: 1. Preparation and coating of slurry of the first electrolyte layer 23 The Li 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP), CMC, SBR and NMP are prepared in a mass ratio of 2:1:7:10 and mixed evenly to obtain a solid electrolyte slurry; the solid electrolyte slurry is coated on the corresponding surface of the base film 1 (using a gravure printing process) to form a 2μm thick first electrolyte layer 23 on the base film 1.

[0084] 2. Preparation and coating of slurry of the second electrolyte layer 24 The Li 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP), CMC, SBR and NMP are prepared in a mass ratio of 2:1:7:10 and mixed evenly to obtain a solid electrolyte slurry; the solid electrolyte slurry is coated on the first electrolyte layer 23 (using a gravure printing process) to form a 2μm thick second electrolyte layer 24 on the surface of the first electrolyte layer 23.

[0085] Example 3-Example 6 The specific parameter settings are shown in Table 1.

[0086] Comparative Example 1 The difference from Example 1 is that the second electrolyte layer 24 is not provided.

[0087] Comparative Example 2 The difference from Example 1 is that the first electrolyte layer 23 is not provided.

[0088] Comparative Example 3 The difference from Example 2 is that the second electrolyte layer 24 is not provided.

[0089] Comparative Example 4 The difference from Example 2 is that the first electrolyte layer 23 is not provided.

[0090] Comparative Example 5 Compared with Example 1, the porosity of the first electrolyte layer 23 is greater than the porosity of the second electrolyte layer 24 .

[0091] It should be noted that the single-layer structure in Comparative Examples 1-4 indicates that the porosity of the electrolyte layer 2 near the base membrane 1 is the same as that of the electrolyte layer 2 far from the base membrane 1. The pore size of the micropores 11 in the above embodiments and comparative examples is 0.05 μm-0.1 μm, and the base membrane 1 is made of polypropylene film.

[0092] The settings of the parameters in the above-mentioned Examples 1-6 and Comparative Examples 1-5 are detailed in Table 1. The composite diaphragms 100 obtained in Examples 1-6 and Comparative Examples 1-5 were tested for relevant properties, and the test results are shown in Table 2.

[0093] Table 1 Settings of various parameters of the composite diaphragm 100 of Examples 1-6 and Comparative Examples 1-4

[0094] Table 2 Performance test results of the composite diaphragm 100 of Examples 1-6 and Comparative Examples 1-4

[0095] As can be seen from Table 2, the thermal shrinkage of the composite diaphragm 100 of Examples 1 to 6 is significantly lower than that of Comparative Examples 1 to 5, indicating that the thermal stability of the composite diaphragm 100 is improved, and the electrical performance and safety performance of the battery are improved. The contact angle of the composite diaphragm 100 of Examples 1 to 6 is significantly smaller than the contact angle of Comparative Examples 1 to 5, indicating that the electrolyte is easy to infiltrate when in contact with the composite diaphragm 100. Compared with Example 1, Comparative Example 5 can significantly improve the thermal stability of the electrolyte layer by setting the porosity of the electrolyte particles 21 close to the side of the base membrane 1 to be smaller than the porosity of the electrolyte particles 21 away from the side of the base membrane 1, thereby improving the electrical performance and safety performance of the battery, and also improving the electrolyte wettability and liquid retention of the composite diaphragm 100. As can be seen from Example 1 compared with Comparative Examples 1 and 2, the composite diaphragm 100 of the present application has better electrolyte wettability and also has better thermal stability.

[0096] Other structures and operations of the battery, battery module, battery pack and vehicle according to the embodiments of the present invention are well known to those skilled in the art and will not be described in detail here.

[0097] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0098] In the description of the present invention, "plurality" means two or more.

[0099] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0100] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A composite diaphragm, characterized in that: include: Basement membrane; An electrolyte layer is provided on at least one surface of the base membrane in the thickness direction, the electrolyte layer comprises electrolyte particles, and the porosity of the electrolyte layer close to the base membrane is smaller than the porosity of the electrolyte layer away from the base membrane.

2. The composite diaphragm according to claim 1, characterized in that: Micropores are formed on the base film, and the maximum width of the electrolyte particles is greater than the maximum width of the micropores.

3. The composite diaphragm according to claim 2, characterized in that: The porosity of the electrolyte layer gradually increases along the direction from the base film to the electrolyte layer.

4. The composite diaphragm according to claim 3, characterized in that: The porosity of the electrolyte layer is v, wherein v satisfies: 20%≤v≤90%.

5. The composite diaphragm according to claim 4, characterized in that: The v satisfies: 30%≤v≤60%.

6. The composite diaphragm according to claim 2, characterized in that: The particle size of the electrolyte particles is d, wherein d satisfies: 0.01 μm≤d≤100 μm.

7. The composite diaphragm according to any one of claims 2 to 6, characterized in that: The particle size of the electrolyte particles on a side close to the base film is smaller than the particle size of the electrolyte particles on a side far from the base film.

8. The composite diaphragm according to claim 7, characterized in that: The particle sizes of the electrolyte particles gradually increase along the direction from the base film to the electrolyte layer.

9. The composite diaphragm according to claim 7, characterized in that: The electrolyte layer comprises at least: A first electrolyte layer, the first electrolyte layer is provided on at least one side surface of the base film in the thickness direction, and the first electrolyte layer includes first electrolyte particles; The second electrolyte layer is disposed on a side of the first electrolyte layer away from the base membrane, and the second electrolyte layer includes second electrolyte particles, wherein the particle size of the second electrolyte particles is larger than that of the first electrolyte particles.

10. The composite diaphragm according to claim 9, characterized in that: The particle size of the first electrolyte particles is d1, wherein d1 satisfies: 0.01 μm≤d1≤3 μm.

11. The composite diaphragm according to claim 9 or 10, characterized in that: The particle size of the second electrolyte particles is d2, wherein d2 satisfies: 1 μm≤d2≤100 μm.

12. The composite diaphragm according to claim 9, characterized in that: A mass proportion of the first electrolyte particles in the first electrolyte layer is greater than a mass proportion of the second electrolyte particles in the second electrolyte layer.

13. The composite diaphragm according to any one of claims 1 to 6, characterized in that: The thickness of the composite diaphragm is h3, wherein h3 satisfies: 0.1 μm≤h3≤1 mm.

14. The composite diaphragm according to any one of claims 1 to 6, characterized in that: The electrolyte layer includes a binder. In terms of mass percentage, the electrolyte layer includes: 0.1% to 99% of the electrolyte particles and 1% to 99.9% of the binder.

15. The composite diaphragm according to claim 14, characterized in that: In terms of mass percentage, the electrolyte layer comprises: 1% to 80% of the electrolyte particles and 20% to 99% of the adhesive.

16. The composite diaphragm according to claim 14, characterized in that: The adhesive includes at least one of vinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, polyethylene oxide, carboxymethyl cellulose, sodium alginate, polyacrylic acid, polyamide, polyvinyl alcohol, polyethylene imine and polyimide.

17. The composite diaphragm according to any one of claims 1 to 6, characterized in that: The electrolyte particles include at least one of an inorganic ceramic oxide solid electrolyte, an organic-inorganic composite solid electrolyte, and an organic polymer solid electrolyte.

18. The composite diaphragm according to claim 17, characterized in that: The inorganic ceramic oxide solid electrolyte includes at least one of a perovskite solid electrolyte, a garnet solid electrolyte, an amorphous oxide solid electrolyte, a lithium superion conductor solid electrolyte and a sodium superion conductor solid electrolyte; and / or, The organic-inorganic composite solid electrolyte includes polyethylene oxide solid electrolyte, oxide-polymer composite solid electrolyte, sulfide-polymer composite solid electrolyte; and / or, The organic polymer solid electrolyte includes a polymer solid electrolyte, a covalent organic framework solid electrolyte, a polycarbonate solid electrolyte, a polyether solid electrolyte or an organic ion crystal electrolyte.

19. The composite diaphragm according to any one of claims 1 to 6, characterized in that: The base film includes at least one of a polyethylene film, a polypropylene film, a polyvinylidene fluoride film, an aramid film, a polyacrylonitrile film, a polyimide film, a polyamide film, a polyester film, and a natural fiber film.

20. A battery, characterized in that: Comprising the composite diaphragm according to any one of claims 1-19.

21. An electrical equipment, characterized in that: Comprising a battery according to claim 20.

Citation Information

Cited By

  • Laminated battery cell and battery

    CN121416753A